Empowering Smallholder Coconut Farmers Through E-Commerce: A Preliminary Study on Current Business Models, Opportunities, and Digital Readiness in Malaysia - Ahmad, Jusoh; Asan Ali, Golam Hassan; Nanthakumar, Loganathan; Mori, Kogid; Hamrila, Abdul Latip; Nor Hidayati, Zakaria; Abdul Razak, Che Hussin; Mohamad Haider, Abu Yazid (Penerbit UTM Press, 2025)
The Malaysian coconut industry is dominated by smallholder farmers who face structural challenges, including low profit margins, reliance on middlemen, and limited access to wider markets. The purpose of this study is to explore the potential of e-commerce adoption to transform the sector by enabling direct market access, increasing price transparency, and supporting value-added processing. A mixed-method approach was employed, comprising focus group discussions (FGDs) and a survey involving 274 coconut farmers and industry stakeholders. The findings reveal two prevailing business models: a traditional middlemen-driven supply chain and a cooperative-led model that supports industrial processing for productslike coconut milk, virgin coconut oil, and copra. While 72.6% of farmers have experience with online purchasing, only 13.5% have attended e-commerce training, indicating a significant digital knowledge gap. Despite these challenges, 71.2% of farmers expressed readiness to adopt e-commerce if supported with proper training, infrastructure, and financial resources. The study highlights the importance of developing a structured and inclusive e-commerce ecosystem facilitated through cooperative engagement, supportive policy frameworks, and targeted investment in digital capacity-building. The results offer practical insights into how digital transformation can enhance the competitiveness and sustainability of Malaysia’s coconut industry while empowering smallholder farmers to improve their economic resilience.